2022
DOI: 10.1002/admi.202200084
|View full text |Cite
|
Sign up to set email alerts
|

Biomass‐Derived Nanoporous Graphene Memory Cell

Abstract: The data that support the findings of this study are available from the corresponding author upon reasonable request.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 64 publications
1
4
0
Order By: Relevance
“…This might be due to the lower V th value observed for lower channel length devices. This is in agreement with our previously reported results on NPG device [22], where we observed that the value of V th for 80 µm and 60 µm devices are lower in comparison to the 100 µm channel length device. As discussed before, the threshold switching in NPG devices arises due to the accumulation of interfacial oxygen ions.…”
Section: Spike Frequency Optimizationsupporting
confidence: 94%
See 3 more Smart Citations
“…This might be due to the lower V th value observed for lower channel length devices. This is in agreement with our previously reported results on NPG device [22], where we observed that the value of V th for 80 µm and 60 µm devices are lower in comparison to the 100 µm channel length device. As discussed before, the threshold switching in NPG devices arises due to the accumulation of interfacial oxygen ions.…”
Section: Spike Frequency Optimizationsupporting
confidence: 94%
“…1(b). The threshold switching behavior of the device is clear from both the figures where the device switches from a high resistance state (HRS) to a low resistance state (LRS) at a threshold voltage (V th ) of 4.9 V and a reverse switching from LRS to HRS at a hold voltage (V hold ) of 0.1 V. Such a volatile switching behavior can be attributed to the oxygen ion accumulation at the interface between the anode and NPG channel [22]. Interestingly, the V hold is very close to 0 V and hence the LRS region spans a wider voltage range (∼4.8 V) which is an added advantage of the NPG device and not seen in previous reports based on 2D material based memristors [20].…”
Section: A Device Descriptionmentioning
confidence: 95%
See 2 more Smart Citations
“…Such adjustable electronic features are highly suited for the emulation of neurological responses. Graphene [ 145 ] has been the most widely studied 2D material, mainly due to its unique electronic and mechanical properties. H. Tian et al [ 146 ] reported the first graphene-based synaptic device having a standard FET configuration and an additional bottom gate electrode.…”
Section: Resistive Switching Materials and Applicationsmentioning
confidence: 99%